Analysis of the Use of Google Translate in the Process of Learning English - Khoirul Alfiyani; Reza Fandana (Jurnal Motivasi Pendidikan dan Bahasa, 2026)
This study aims to analyze the use of Google Translate in the process of learning English, highlighting its benefits, limitations, and impact on students’ learning quality. This research employs a qualitative approach using a library research method, where data are obtained from various literature sources such as books, scholarly articles, and relevant online publications. The findings indicate that Google Translate is widely used by students as a tool to quickly and practically understand English texts. However, this high level of usage also leads to several issues, including the inaccuracy of translations in certain contexts, increased dependency on technology, and a limited understanding of language structure. Nevertheless, Google Translate still provides advantages in improving learning efficiency and access to global knowledge resources. Therefore, the use of this technology needs to be guided wisely so that it supports the learning process without reducing students’ cognitive engagement. This study is expected to contribute to a better understanding of the role of technology in language learning in the digital era and to serve as a reference for educators and students in utilizing technology more effectively.